2021
DOI: 10.3389/fmed.2021.773806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Continuing Medical Education—Results of an Online Survey Among Users of a Non-profit Multi-Specialty Live Online Education Platform

Abstract: Background: The Coronavirus Disease-2019 (COVID-19) pandemic accelerated digitalization in medical education. Continuing medical education (CME) as a substantial component of this system was relevantly affected. Here, we present the results of an online survey highlighting the impact on and the role of online CME.Methods: An online survey of 44 questions was completed by users of a German online CME platform receiving an invitation via newsletter. CME habits, requirements, personal perception, and impact of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Note that the present study shows that, in relation to the GPs' learning preferences and needs, the online method was not their preferred choice. However, if CME is mandatory, online would be their first option, and in the future, the acceptance of computer-based internet or online education will increase markedly worldwide [ 16 , [40] , [41] , [42] ]. Therefore, if they must undertake CME to maintain their registration, the most flexible and suitable method to adopt for their busy practice may be online.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the present study shows that, in relation to the GPs' learning preferences and needs, the online method was not their preferred choice. However, if CME is mandatory, online would be their first option, and in the future, the acceptance of computer-based internet or online education will increase markedly worldwide [ 16 , [40] , [41] , [42] ]. Therefore, if they must undertake CME to maintain their registration, the most flexible and suitable method to adopt for their busy practice may be online.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers utilize modern information technology to their advantage and compile content and knowledge points into vivid and convenient micro-videos. Students tend to use emerging technologies as tools to acquire new knowledge ( 108 ). Digital experience has become a part of the learning habits of the new generation of students ( 109 ).…”
Section: Resultsmentioning
confidence: 99%
“…5,12 Recent studies that have investigated physicians' perceptions of virtual CME alternatives prompted by the pandemic have also identified that participants prefer hybrid (face-to-face and online) formats and that virtual offerings should not replace but complement traditional in-person offerings. 3,[13][14][15] These perspectives, along with our observations, may help inform future 6 This mid-career age group in particular could be a target for a range of highly flexible, on-demand approaches to CME.…”
Section: Discussionmentioning
confidence: 98%
“…CME is delivered through a variety of modalities and approaches, frequently evolving due to many factors, 2 , 3 and further catalyzed by the COVID‐19 pandemic. The number of accredited CME activities offered continues to grow with approximately 179,000 activities reported in 2018 increasing to nearly 189,000 activities in 2019.…”
Section: Introductionmentioning
confidence: 99%